ULTRASTRUCTURAL CHANGES IN RAT SCIATIC NERVE AFTER HEMORRHAGIC STROKE - Dovgan, I.M. (World of Medicine and Biology, 2019)
The changes in the sciatic nerve after local hemorrhagic stroke modeling were studied. The hemorrhagic stroke in Wistar rats was modeled through the autologous blood injection into internal capsule of the right cerebral hemisphere. In experiment were included 3 groups of animals: intact rats (group 1, n=10), rats with stroke during 10 days of observation (group 2, n=12) and rats with stroke during 30 days of observation (group 3, n=10). The sciatic nerve was examined by electron microscopy. The morphometric method has been used for measurement of diameter of myelinated and unmyelinated nerve fibers in sciatic nerves. On 10th and 30th day after stroke the left and right sciatic nerves were studied and compared a morphometric data. The bilateral nerve degeneration with the damaged nerve fibers was established. The acute edema of myelin shell and deformation of the axial cylinder were the typical ultrastructural changes after stroke in group 2 and 3. Some myelinated nerve fibers were characterized by the increased electron density of axoplasm which indicated atrophy and degeneration of them. At the same time, changes in unmyelinated nerve fibers were much less pronounced and often remained intact. The damage was limited mild swelling of axoplasm and reduction of axoplasmic organelles, cytoskeleton elements. Stromal elements of the nerve, in particular collagen fibers and fibroblasts, have not been disrupted. There was no significant difference in the changes of the myelin shell of nerve fibers between the right and left sciatic nerves. Diameter of nerve fibers in intact and experimental groups was analyzed during morphometric method. The diameter of myelinated fibers in the left and right nerves decreased by 20.5% and 18.3% (p